PENGARUH PENGGUNAAN BENIH BERSERTIFIKAT TERHADAP EFISIENSI TEKNIS USAHATANI BAWANG PUTIH - Lalu Hendri Setiawan; Amzul Rifin; Harmini (Jurnal Penelitian Pertanian Terapan, 2023)
The use of certified seeds can increase productivity and technical efficiency of garlic farming. This study aimed to examine the effect of using certified seeds on the technical efficiency and productivity of garlic farming. This study uses secondary data in the form of cross-sections from the Horticultural Plant Household Survey (SHR, 2014) conducted by the Central Bureau of Statistics (BPS). The number of samples used is the same as the number of SHR 2014 samples. These data were analyzed using stochastic production frontier sample correction (SC-SPF) combined with propensity score matching (PSM) to eliminate observed and unobserved biases. The average treatment effect on the treated (ATET) used to directly calculate the effect of using certified seeds on productivity and technical efficiency. The average productivity of farmers using certified seeds was higher than that of farmers who did not use certified seeds. Meanwhile, the average technical efficiency (ET) of farmers who use certified seeds is lower than that of farmers who do not use certified seeds. This shows that the use of certified seeds has no effect on the technical efficiency of garlic farming. There are two alternative policies that can be taken, the first is advising farmers not to use certified seeds or the second alternative is improving the mechanism for distributing garlic seed assistance and developing the garlic seed industry.